A method for preparing a polyimide fiber / graphene composite aerogel having a vertically oriented pore structure
Patent Information
- Application Number
- CN202210977914.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-16
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2042-08-16
AI Technical Summary
尽管传统的电磁波吸收纳米材料(如Fe、Fe3O4、碳、碳纳米管)在磁损耗或介电损耗方面取得了巨大进展,但其密度高、吸收弱以及其他缺点,如纳米结构的合成过程复杂,以及在大规模生产中面临的挑战,严重阻碍了其发展和大规模使用
[0019]本发明通过冰模板,冷冻干燥和高温热处理三步法,制备以聚酰亚胺纤维为骨架的聚酰亚胺纤维/石墨烯复合气凝胶,所得气凝胶呈薄片状,内部具有垂直取向的孔隙结构,预冷铜板的温度不同,所得气凝胶的孔隙尺寸不同,聚酰亚胺纤维相互缠绕形成骨架被石墨烯紧紧包裹,形成完整的石墨烯导电网络,使得气凝胶具有很好的回弹性及力学性能和电磁波吸收性能。
Smart Images

Figure HSA0000281248390000011 
Figure HSA0000281248390000012 
Figure HSA0000281248390000021
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure, belonging to the field of microwave absorbing materials. Background Technology
[0002] Since breakthroughs in wireless communication technology, a plethora of new wirelessly connected devices have emerged, particularly the Internet of Things (IoT), artificial intelligence (AI), wearable electronics, and microwave sensors. These devices have revolutionized society, paving the way for the intelligent era. While the rapid development of wireless technology has improved our quality of life, the widespread use of wireless electronics has inevitably led to severe electromagnetic pollution, now considered the fourth largest source of pollution after air, water, and noise pollution. The hazards of electromagnetic pollution mainly include two aspects: negative impacts on human health and interference with the operation of nearby electronic devices, causing signal loss or interruption, also known as electromagnetic interference (EMI). Compared to physical hazards, EMI is becoming increasingly prominent because it not only limits the performance of advanced electronic products, potentially leading to significant economic losses, but also hinders the development of emerging fields. As modern electronic devices operate at frequencies concentrated in narrowband (2-6.0 GHz), conflicts between these electromagnetic signals are intensifying. For example, devices built on current wireless charging technology often suffer from slow charging speeds and poor energy efficiency, primarily due to signal interference from other devices. Similarly, other promising applications, such as autonomous vehicles or aircraft, and remote surgery, remain significant challenges until the problems caused by EMI are overcome.
[0003] The key performance indicators for excellent electromagnetic wave absorbers are high reflection loss, thinness, wide bandwidth, and low density. This is because such materials can absorb most electromagnetic waves and are likely to be practically used. Recently, a large number of nanomaterials (such as magnetic materials, carbon materials, and magnetic carbon composites) have emerged, and their electromagnetic wave absorption performance has been improved by controlling their size, shape, internal structure, and composition. Although traditional electromagnetic wave absorbing nanomaterials (such as Fe, Fe3O4, carbon, and carbon nanotubes) have made great progress in terms of magnetic or dielectric loss, their high density, weak absorption, and other drawbacks, such as the complex synthesis process of nanostructures and the challenges faced in large-scale production, seriously hinder their development and large-scale application.
[0004] Graphene, due to its extremely high specific surface area, light weight, and ease of dielectric tuning, has been proven to be the best choice for microwave absorbing materials. Pure graphene is extremely prone to impedance mismatch; therefore, modified graphene oxide is used. By introducing functional groups and defects, it can improve the loss of electromagnetic waves. Preparing it in the form of an aerogel, which contains a large amount of air, not only increases impedance matching but also gives the material an extremely low density. The oriented porous structure can improve the responsiveness to electromagnetic waves, making it easier for electromagnetic waves to enter the material's interior. The presence of a three-dimensional conductive graphene network has a strong ability to attenuate electromagnetic waves.
[0005] Therefore, designing and preparing a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure is of great significance. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing polyimide fiber / graphene composite aerogel with a vertically oriented pore structure. The polyimide fibers are intertwined to form a skeleton, which is tightly wrapped by graphene sheets to form a complete graphene conductive network, so that the aerogel has good resilience, mechanical properties and electromagnetic wave absorption properties.
[0007] The present invention adopts the following technical solution:
[0008] This invention relates to a method for preparing a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure, the steps of which are as follows:
[0009] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 0.8-1.2 mol / L, and stir at 40℃ for 2-2.5 h to ensure uniform dispersion and surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0010] 2) Preparation of polyimide fiber / graphene composite aerogel: A certain concentration of graphene oxide aqueous solution was mixed with polyimide fiber at a certain mass ratio, and the mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a pre-frozen copper plate. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48–60 hours.
[0011] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and subjected to high-temperature heat treatment in an argon and hydrogen atmosphere. During this process, cross-linking of the polyimide fibers and reduction of graphene oxide occur. After holding at the final temperature for a period of time, it is allowed to cool naturally to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
[0012] Preferably, the alkaline solution in step 1) can be either sodium hydroxide or potassium hydroxide.
[0013] Preferably, in step 2), the mass ratio of polyimide fiber to graphene is 0.4:1, 0.5:1, 0.6:1, or 0.7:1.
[0014] Preferably, the concentration of the graphene oxide aqueous solution in step 2) is 4–8 mg / ml.
[0015] Preferably, the temperature of the pre-frozen copper plate in step 2) is -50 to -80°C.
[0016] Preferably, the heating rate in step 3) of the heat treatment process is 5-8°C / min.
[0017] Preferably, the final temperature of the heat treatment process in step 3) is 400–700°C.
[0018] Preferably, in step 3), the holding time after the heat treatment process reaches the final temperature is 20-30 minutes.
[0019] This invention prepares a polyimide fiber / graphene composite aerogel with polyimide fiber as the skeleton through a three-step method of ice template, freeze drying and high temperature heat treatment. The resulting aerogel is in the form of a thin sheet with a vertically oriented pore structure inside. The pore size of the aerogel varies depending on the temperature of the pre-cooled copper plate. The polyimide fibers are intertwined to form a skeleton that is tightly wrapped by graphene, forming a complete graphene conductive network. This gives the aerogel excellent resilience, mechanical properties and electromagnetic wave absorption properties. Attached Figure Description
[0020] Figure 1 This is a sample image of a polyimide fiber / graphene oxide composite aerogel.
[0021] Figure 2 A cross-sectional scanning electron microscope image of a polyimide fiber / graphene composite aerogel heat-treated at 400℃;
[0022] Figure 3 The image shows the 80% strain cycle curve of the aerogel (polyimide fiber: graphene = 0.5:1) obtained in this invention. Detailed Implementation
[0023] The following six embodiments of the present invention are provided to further illustrate the invention, but are not intended to limit the scope of the invention.
[0024] Example 1
[0025] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 1 mol / L, stir at 40℃ for 2 h to ensure uniform dispersion, and perform surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0026] 2) Preparation of polyimide fiber / graphene composite aerogel: Polyimide fibers and graphene oxide were mixed at a mass ratio of 0.3:1, and the concentration of the graphene oxide aqueous solution used was 4 mg / ml. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen to -60°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48 hours.
[0027] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and heated to 400℃ at a heating rate of 5℃ / min under an argon and hydrogen atmosphere. After holding at 400℃ for 30 min, it is naturally cooled. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. After holding at the final temperature for a period of time, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
[0028] Example 2
[0029] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 1 mol / L, stir at 40℃ for 2 h to ensure uniform dispersion, and perform surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0030] 2) Preparation of polyimide fiber / graphene composite aerogel: Polyimide fibers and graphene oxide were mixed at a mass ratio of 0.4:1, and the concentration of the graphene oxide aqueous solution used was 7 mg / ml. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen to -80°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48 hours.
[0031] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and heated to 600℃ at a heating rate of 5℃ / min under an argon and hydrogen atmosphere. After holding at 600℃ for 20min, it is naturally cooled. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. After holding at the final temperature for a period of time, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
[0032] Example 3
[0033] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 1 mol / L, stir at 40℃ for 2 h to ensure uniform dispersion, and perform surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0034] 2) Preparation of polyimide fiber / graphene composite aerogel: Polyimide fibers and graphene oxide were mixed at a mass ratio of 0.5:1, and the concentration of the graphene oxide aqueous solution used was 5 mg / ml. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen to -70°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48 hours.
[0035] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and heated to 500℃ at a heating rate of 5℃ / min under an argon and hydrogen atmosphere. After holding at 500℃ for 30 min, it is naturally cooled. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. After holding at the final temperature for a period of time, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
[0036] Example 4
[0037] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 1.2 mol / L, stir at 40℃ for 2 h to ensure uniform dispersion, and perform surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0038] 2) Preparation of polyimide fiber / graphene composite aerogel: Polyimide fibers and graphene oxide were mixed at a mass ratio of 0.7:1, and the concentration of the graphene oxide aqueous solution used was 6 mg / ml. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen to -70°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48 hours.
[0039] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and heated to 600℃ at a heating rate of 5℃ / min under an argon and hydrogen atmosphere. After holding at 600℃ for 25min, it is naturally cooled. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. After holding at the final temperature for a period of time, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
[0040] Example 5
[0041] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 1.2 mol / L, stir at 40℃ for 2 h to ensure uniform dispersion, and perform surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0042] 2) Preparation of polyimide fiber / graphene composite aerogel: Polyimide fibers and graphene oxide were mixed at a mass ratio of 0.3:1, and the concentration of the graphene oxide aqueous solution used was 6 mg / ml. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen to -60°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48 hours.
[0043] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and heated to 400℃ at a heating rate of 8℃ / min under an argon and hydrogen atmosphere. After holding at 400℃ for 20min, it is naturally cooled. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. After holding at the final temperature for a period of time, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
[0044] Example 6
[0045] 1) Polyimide fiber modification treatment: Disperse polyimide chopped fibers in an alkaline solution with a concentration of 1.2 mol / L, stir at 40℃ for 2 h to ensure uniform dispersion, and perform surface modification. Then wash, centrifuge with deionized water until neutral, and then freeze-dry to obtain the modified polyimide fibers.
[0046] 2) Preparation of polyimide fiber / graphene composite aerogel: Polyimide fibers and graphene oxide were mixed at a mass ratio of 0.5:1, and the concentration of the graphene oxide aqueous solution used was 8 mg / ml. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen to -60°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48 hours.
[0047] 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and heated to 500℃ at a heating rate of 8℃ / min under an argon and hydrogen atmosphere. After holding at 500℃ for 30 min, it is naturally cooled. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. After holding at the final temperature for a period of time, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
Claims
1. A method for preparing a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure, characterized in that: The preparation steps are as follows: 1) Polyimide fiber modification treatment: Disperse polyimide short-cut fibers in an alkaline solution with a concentration of 0.8-1.2 mol / L, stir at 40℃ for 2-2.5 h to make the dispersion uniform, and perform surface modification; The fibers were then washed, centrifuged with deionized water until neutral, and then freeze-dried to obtain the modified polyimide fibers. 2) Preparation of polyimide fiber / graphene composite aerogel: A 4-8 mg / ml aqueous solution of graphene oxide was mixed with polyimide fiber at a mass ratio of 0.4:1, 0.5:1, 0.6:1 or 0.7:
1. The mixture was ultrasonically treated to ensure uniform dispersion. The mixture was then poured into a quartz mold with its bottom in contact with a copper plate pre-frozen at -50 to -80°C. Ice crystals began to grow vertically from the bottom, forming vertically and regularly arranged ice fingers. The mold was then transferred to a freeze dryer and freeze-dried for 48-60 hours. 3) Heat treatment of the freeze-dried polyimide fiber / graphene oxide composite aerogel: The polyimide fiber / graphene oxide composite aerogel is placed in a vacuum tube furnace and subjected to high-temperature heat treatment in an argon and hydrogen atmosphere. The temperature is raised to 400-700℃ at a heating rate of 5-8℃ / min and held at the final temperature for 20-30min. During this process, cross-linking of polyimide fibers and reduction of graphene oxide will occur. Then, it is naturally cooled to obtain a polyimide fiber / graphene composite aerogel with a vertically oriented pore structure.
2. The preparation method according to claim 1, characterized in that: The alkaline solution mentioned in step 1) is either a sodium hydroxide solution or a potassium hydroxide solution.
3. The preparation method according to claim 1, characterized in that: The concentration of the graphene oxide aqueous solution in step 2) is 4 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml or 8 mg / ml.
4. The preparation method according to claim 1, characterized in that: The final temperature of the heat treatment process described in step 3) is 400℃, 500℃, 600℃ or 700℃.
5. The polyimide fiber / graphene composite aerogel prepared by any one of the preparation methods of claims 1-4, characterized in that, Its shape is thin sheet, and its interior has a vertically oriented porous structure. Polyimide fibers are intertwined to form a skeleton, which is tightly wrapped by graphene sheets to form a complete graphene conductive network, giving the aerogel excellent resilience, mechanical properties and electromagnetic wave absorption properties.
6. The aerogel as described in claim 5, characterized in that... The pore size of the aerogel changes with the temperature of the pre-frozen copper plate.
Citation Information
Patent Citations
Polymer or polymer composite membrane having through-thickness micropores, and method for preparing same
US20120325737A1
High elastic deformation sensing graphene composite material, preparation method therefor, and use thereof
WO2018218930A1